Head orientation tracking using binaural headset microphones - Gamper, Hannes; Tervo, Sakari; Lokki, Tapio (Proceedings of the Audio Engineering Society Convention, 2011)
A head orientation tracking system using binaural headset microphones is proposed. Unlike previous approaches, the proposed method does not require anchor sources, but relies on speech signals of the wearers of the binaural headsets. From the binaural microphone signals, time of arrival (TOA) and time difference of arrival (TDOA) estimates are obtained. The tracking is performed using a particle filter integrated with a maximum likelihood estimation function. In a case study, the proposed method is used to track the head orientations of three conferees in a meeting scenario. With an accuracy of about 10 degrees, the proposed method is shown to outperform a reference method which achieves an accuracy of about 35 degrees.
Paper no. 8538